1165 Reporting Patient Selection in Robotic Cholecystectomy: Less than IDEAL? A Systematic Review. (12th October 2021) - Biggs, S; Dixon, L; Brankin-Frisby, T; Dewi, F; Torkington, A; Olivier, J; Kirkham, E
Abstract: Introduction: Laparoscopic cholecystectomy is the gold standard definitive treatment option for benign biliary disease. There has been increasing interest in novel robotic surgical techniques; robotic cholecystectomy (RC) represents the most recent innovation in the management of gallstones. The IDEAL Collaboration has provided guidance for the rigorous and comprehensive reporting of surgical innovations, despite this, transparency in patient selection has been limited. We aimed to assess the reporting of patient selection in studies reporting RC. Method: A collaborative, systematic review was conducted in accordance with the PRISMA guidance to identify all published studies reporting RC. Study specific inclusion and exclusion criteria were detailed in a protocol. Results: Searches identified 1425 abstracts; 90 papers were included for data extraction. Inclusion criteria were reported in 38 (42%) studies. The most frequently cited were age (20%), aetiology (20%), presence of symptoms (16%) and comorbidities (10%). Forty-nine (54%) studies reported exclusion criteria. Numerous and variably reported exclusion criteria were reported; acute cholecystitis (26%), previous abdominal surgery (25%), comorbidity (17%), pregnancy (13%), common bile duct stones (13%) and pancreatitis (10%) among others. Seven reported no exclusion criteria. Three reported numbers of patients who declined RC. Conclusions: Patient selection criteria were inconsistently reported and when present lacked standardisation. Concern persists around patients being "cherry picked" for inclusion in studies reporting innovative robotic surgical procedures, making interpretation and applicability of results impossible. Standardised inclusion criteria are needed to enable greater transparency and reproducibility to ensure the safe adoption of new technologies into clinical practice.